2022
DOI: 10.3390/ijerph191711106
|View full text |Cite
|
Sign up to set email alerts
|

Association between Maternal Anxiety and Children’s Problem Behaviors: A Systematic Review and Meta-Analysis

Abstract: Although numerous studies have found that maternal anxiety is a risk factor for the development of children’s problem behaviors, and there is a possible role of genes in the association between the two. And anxious mothers caring for their children can also affect the development of children’s problem behaviors. However, there is also considerable evidence from studies that refute this view. This study used a meta-analysis to explore the relationship between maternal anxiety and preschool children’s problem be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…A recent Brazilian study reported that mothers presented similar educational and care strategies for boys and girls, although girls had presented more internalizing behavioral problems (e.g., anxiety and depression) than boys (Maia & Soares, 2018). It is suggested that mothers display more negative educational practices and anxiety when the child who exhibits behavioral problems is a girl than when it is a boy (Maia & Soares, 2018;Song et al, 2022). The combination of conflicts with parents experienced during adolescence and behavioral difficulties may negatively affect parenting, leading mothers and/or fathers to become more overprotective and express lower levels of care (Forresi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A recent Brazilian study reported that mothers presented similar educational and care strategies for boys and girls, although girls had presented more internalizing behavioral problems (e.g., anxiety and depression) than boys (Maia & Soares, 2018). It is suggested that mothers display more negative educational practices and anxiety when the child who exhibits behavioral problems is a girl than when it is a boy (Maia & Soares, 2018;Song et al, 2022). The combination of conflicts with parents experienced during adolescence and behavioral difficulties may negatively affect parenting, leading mothers and/or fathers to become more overprotective and express lower levels of care (Forresi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…We adopted the definition of behavioral problems by Chinese scholars, which tends to have the following viewpoints: behavioral problems are all abnormal behaviors that hinder individual and social development, involving externalizing and internalizing behavioral problems. The core point is that difficult adaptation behaviors produced in the process of socialization for children and adolescents [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, male sex of the child was associated with increased symptoms of anxiety and depression in mothers. Literature shows heterogeneous results for the interplay between maternal and child mental health and child sex [31,32]. However, when maternal CM is taken into account, a greater vulnerability for boys was shown before for the indirect effects of maternal CM via anxiety and depression [33].…”
Section: Sdq: Child Behaviour DI Cultiesmentioning
confidence: 99%
“…Sex is known to signi cantly affect the development of psychopathology, as there are relevant gender differences regarding mental health problems [34]. Child sex is further suggested to moderate the effect of maternal and child mental health [32].…”
Section: Sdq: Child Behaviour DI Cultiesmentioning
confidence: 99%